Thermal functions of internal courtyards in traditional Chinese shophouses in the hot-humid climate of Malaysia - Kubota, Tetsu; Zakaria, Mohd Azuan; Abe, Seiji; Toe, Doris Hooi Chyee (Elsevier, 2017)
The main purpose of this study was to identify the thermal functions of internal courtyards in traditional Chinese shophouses (CSHs) located in the hot-humid climate of Malaysia with the aim of providing useful passive cooling strategies for modern urban houses. The CSHs are deep-plan brick row houses that are located in relatively dense urban areas. First, this paper empirically analyses the effects of courtyard forms on their indoor thermal environments based on the results of field experiments conducted in 16 CSHs in the city of Malacca in 2011 and 2014. Second, this paper investigates the detailed thermal environments of the selected two traditional CSHs with different courtyard types to discuss the thermal functions of courtyards. It was determined that air temperatures in internal courtyards can be explained using the sky view factor, the height of the courtyard and the difference in the heights of the building and walls that form the courtyard. The courtyard forms that characterized their thermal environments were classified into five types and the different types of courtyards performed different functions with respect to improving the indoor thermal comfort in the CSHs. It was suggested that closed, cross ventilated courtyards be embedded to achieve indoor thermal comfort and avoid excessive humidity in hot-humid climates. Meanwhile, it was also recommended that a staggered form courtyard with V-shaped roofs should be designed as a nocturnal cooling source.